Pendekatan Strategik Mengelola Perubahan Organisasi - Retno Wulandari (Jurnal Aplikasi Bisnis, 2017)
If businesses are to survive, leaders must have anticipatory capability, flexibility, and adaptability when adjusting to major changes. But, it is not easy to make change successfully because of many forces facing by leaders. Change will always cause discomfort and dislocation for member of organization. This paper focuses on strategic element and practical solution to ensure implementation success. Developing readiness for planning will reduce participant unprepared to deal with change. Furthermore, leaders must recognize, guide, and support people in their organization to make change initiative.